1982
DOI: 10.1002/1097-0142(19821201)50:11<2524::aid-cncr2820501145>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

The total thigh and rectus abdominis myocutaneous flap for closure of extensive hemipelvectomy defects

Abstract: Hemipelvectomy is a lifesaving procedure when used appropriately and yields a 35%, five‐year survival in the cancer patient. However, the standard posterior flap for closure is not always available. Two flaps, the thigh flap and the rectus abdominis myocutaneous flap, are described in which any soft tissue defect resulting from hemipelvectomy can be safely closed primarily when the posterior flap is not available. The total rectus abdominis flap is previously undescribed and unique in its application. These te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…A fillet flap using the majority of the thigh musculature can be designed as a variation of the anterior hemipelvectomy flap. 19 The anterior hemipelvectomy flap is an axial pattern flap based on the common and superficial femoral arteries and branches of the profunda femoris complex such as the lateral circumflex artery that provide a vigorous blood supply. 10,20 The skin of the anterior thigh to the level of the knee is innervated by the lateral and anterior femoral cutaneous nerves.…”
Section: Discussionmentioning
confidence: 99%
“…A fillet flap using the majority of the thigh musculature can be designed as a variation of the anterior hemipelvectomy flap. 19 The anterior hemipelvectomy flap is an axial pattern flap based on the common and superficial femoral arteries and branches of the profunda femoris complex such as the lateral circumflex artery that provide a vigorous blood supply. 10,20 The skin of the anterior thigh to the level of the knee is innervated by the lateral and anterior femoral cutaneous nerves.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of the fl ap are its abundant supply of well-vascularized tissue, reliability, versatility, and the simplicity of dissection. [100][101][102] Some authors reported the use of the opposite fl ap to reduce complications. 98 In patients with anterior abdominal ostomies, this fl ap is often unavailable.…”
Section: A 11bmentioning
confidence: 99%
“…Unconventional closure techniques include island pedicle flaps, such as that of the ipsilateral rectus abdominis muscle, pedicled on the inferior epigastric vessels and mobilized and tunneled through a narrow abdominal skin bridge [9,16,22]. Another pedicled flap is that of the external oblique muscle, receiving its blood supply from the last six intercostal arteries, which can be rotated inferiorly to cover the defect [3].…”
Section: Discussionmentioning
confidence: 99%
“…Another pedicled flap is that of the external oblique muscle, receiving its blood supply from the last six intercostal arteries, which can be rotated inferiorly to cover the defect [3]. These relatively tedious surgeries, however, are accompanied by complications, such as serous leaks, hematoma, abscess formation, and flap failure [9,16,22], and sometimes also require the need for split thickness skin grafting of the donor site and increased operative time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation